Ocean Acidification Amplifies Multi-Stressor Impacts on Global Marine Invertebrate Fisheries - Tai, Travis C.; Sumaila, U. Rashid; Cheung, William W. L. (Frontiers in Marine Science, 2021)
Elevated atmospheric carbon dioxide (CO2) are causing global ocean changes and driving changes in organism physiology, life history traits, and population dynamics of natural marine resources. However, our knowledge of the mechanisms and consequences of ocean acidification (OA)—in combination with other stressors (i.e. warming, deoxygenation)—on organisms and downstream effects on marine fisheries is limited. Here, we explored how the direct effects of multiple stressors on organism aerobic performance scales up to spatial impacts on fisheries catch of 210 commercially exploited marine invertebrates, the species group known to be susceptible to ocean acidification. Under the highest CO2 trajectory, we show that global fisheries catch potential declines by as much as 12% by the year 2100 relative to present, of which 3.4% was attributed to OA. Moreover, OA effects are exacerbated in areas with greater changes in pH (e.g. West Arctic basin) but show minor effects in tropical areas where the effects of ocean warming are more pronounced (e.g. Indo-Pacific). Our results enhance our knowledge on multi-stressor effects on marine resources and how they can be scaled from physiology to population dynamics. Furthermore, it underscores variability of responses to OA and identifies vulnerable regions and species.